Study on optimization of compressive properties of phosphorus gypsum-blast furnace slag-phosphorus tailings unburned brick - Jianli Wang; ShengqingWang; Biyang Tuo (Scientific Reports)
Abstract The comprehensive utilization of phosphogypsum, phosphorus tailings, and blast-furnace slag is of great significance to environmental protection, resource conservation, and economic development. This study utilized phosphogypsum-blast furnace slag cold-bonded aggregate (PBCA) as the aggregate; β-hemihydrate phosphogypsum (β-HPG), blast furnace slag (BS), and phosphate tailings (PT) as raw materials; along with polycarboxylate superplasticizer (PS) and vinyl acetate-ethylene copolymer re-dispersible latex powder (EVA) as admixtures to produce phosphogypsum-blast furnace slag-phosphorus tailings unburned bricks (PBPB). The mechanical properties of the unburned bricks were optimized through single-factor experiments. Ca(OH)2 is formed from CaO and water in blast-furnace slag and cement, and Ca(OH)2 reacts with silica-aluminum oxide to form calcium silicate, calcium aluminate, and calcium aluminosilicate, which strengthens the unburned bricks. The study found that with a ratio of β-HPG: BS = 8:2, a polycarboxylate superplasticizer content of 0.9 wt%, an EVA content of 1.5 wt%, and phosphate tailings and PBCA contents of 10 wt% and 80 wt%, respectively, the 28-day strength of unburned bricks reached 24.3 MPa. XRD and SEM analyses revealed that the hydration products primarily consisted of gypsum, ettringite, and hydrated calcium silicate (C-S-H gel), which increase the compactness of the blocks and thus improve the strength.